2021
DOI: 10.1063/5.0037594
|View full text |Cite
|
Sign up to set email alerts
|

In silico design of a new Zn–triazole based metal–organic framework for CO2 and H2O adsorption

Abstract: In search for future good adsorbents for CO2 capture, a nitrogen-rich triazole-type Metal–Organic Framework (MOF) is proposed based on the rational design and theoretical molecular simulations. The structure of the proposed MOF, named Zinc Triazolate based Framework (ZTF), is obtained by replacing the amine-organic linker of MAF-66 by a triazole, and its structural parameters are deduced. We used grand-canonical Monte Carlo (GCMC) simulations based on generic classical force fields to correctly predict the ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…GCMC simulations reveal that H2O molecules enhanced the CO2 adsorption at very low pressures; simultaneously, there is a reduction of CO2 adsorption at higher pressures [216] . H2O and SO2 exhibited a cooperative effect on CO2 adsorption for ZIF-NO2 and ZIF-90 containing polar functional groups [217] .…”
Section: Gases Loading and Interferencesmentioning
confidence: 94%
See 1 more Smart Citation
“…GCMC simulations reveal that H2O molecules enhanced the CO2 adsorption at very low pressures; simultaneously, there is a reduction of CO2 adsorption at higher pressures [216] . H2O and SO2 exhibited a cooperative effect on CO2 adsorption for ZIF-NO2 and ZIF-90 containing polar functional groups [217] .…”
Section: Gases Loading and Interferencesmentioning
confidence: 94%
“…A computational study using GCMC simulations were reported to study the adsorption of CO2 and H2O using the Zinc Triazolate-based Framework (ZTF) [216] . Data analysis reveals that the interactions between ZTF and CO2 occur via two sites; Lewis acid-Lewis base interactions and hydrogen bonding, together with apparent electrostatic interactions [216] . In situ Raman investigation was reported to study the interactions of ZIFs with CO2 under pressure (0-10 bar)…”
Section: Mechanism Of Co2 Adsorption Into Zifs Materialsmentioning
confidence: 99%
“…GCMC simulations reveal that H 2 O molecules enhanced the CO 2 adsorption at very low pressures; simultaneously, there is a reduction of CO 2 adsorption at higher pressures. [ 216 ] H 2 O and SO 2 exhibited a cooperative effect on CO 2 adsorption for ZIF‐NO 2 and ZIF‐90 containing polar functional groups. [ 217 ] The presence of gases such as O 2 shows no impact on the capture of CO 2 .…”
Section: Adsorption Of Co2mentioning
confidence: 99%
“…[ 216 ] Data analysis reveals that the interactions between ZTF and CO 2 occur via two sites: Lewis acid–Lewis base interactions and hydrogen bonding, together with apparent electrostatic interactions. [ 216 ] In situ Raman investigation was reported to study the interactions of ZIFs with CO 2 under pressure (0–10 bar) and temperature regimes (0°C to 64°C). [ 227 ] Raman spectra show a significant shift (159 cm −1 ) in the vibration peaks of phenyl bending mode, revealing the presence of HB interaction (Figure 11).…”
Section: Adsorption Of Co2mentioning
confidence: 99%
See 1 more Smart Citation